Search Method Use by Unemployed Youth - Holzer, Harry J. (Journal of Labor Economics, 1988)
This article presents a search model which shows that search method choices should be related to their costs and expected productivities as well as to nonwage income and wage offer distributions. The empirical evidence then shows that the most frequently used search methods (i.e., friends and relatives and direct applications without referral) are also the most productive in generating offers and acceptances. The number of methods used is affected by factors that presumably reflect opportunities as well as income sources and needs. Specific methods are chosen in a manner that generates positive average effects on outcomes for those using them. Copyright 1988 by University of Chicago Press.